ANALYSIS OF STUDENTS' PARENTS' NEEDS IN PREPARING INCLUSIVE PROGRAMS AT ELEMENTARY SCHOOL LEVEL IN TARAKAN CITY - Emmy Ardiwinata; Cici Ismuniar (Jurnal Konseling Pendidikan Islam, 2026)
Inclusive education is a strategic effort to achieve equal access to education for all children, including those with special needs. However, its implementation in Tarakan City still faces various obstacles, particularly in meeting parents' needs for appropriate, child-friendly, and adaptive educational services to the diversity of student abilities. This study aims to analyze the primary needs of parents of students with special needs in the implementation of inclusive education in Tarakan City. The approach used is descriptive qualitative with research locations in several elementary and secondary schools that provide inclusive education in Tarakan City. Research informants included parents of students with special needs, accompanying teachers, and school officials selected by purposive sampling. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation studies, then analyzed using thematic analysis through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the needs of parents of students with special needs include five main indicators: school safety and comfort, teacher competence in handling students with special needs, curriculum flexibility that allows for learning differentiation, the availability of facilities and infrastructure that support inclusive learning, and social support and policies that favor children with special needs. These five indicators show that the ideal implementation of inclusive education requires not only equal access, but also a quality, adaptive, and equitable education system, with policy support and active collaboration between local governments, schools, teachers, and the community.